Oleuropein isolated from Fraxinus rhynchophylla inhibits glutamate-induced neuronal cell death by attenuating mitochondrial dysfunction. (9th August 2018) - Kim, Mi Hye; Min, Ju-Sik; Lee, Joon Yeop; Chae, Unbin; Yang, Eun-Ju; Song, Kyung-Sik; Lee, Hyun-Shik; Lee, Hong Jun; Lee, Sang-Rae; Lee, Dong-Seok
Abstract : Glutamate-induced neurotoxicity is related to excessive oxidative stress accumulation and results in the increase of neuronal cell death. In addition, glutamate has been reported to lead to neurodegenerative diseases, including Parkinson's and Alzheimer's diseases.It is well known that Fraxinus rhynchophylla contains a significant level of oleuropein (Ole), which exerts various pharmacological effects. However, the mechanism of neuroprotective effects of Ole is still poorly defined. In this study, we aimed to investigate whether Ole prevents glutamate-induced toxicity in HT-22 hippocampal neuronal cells. The exposure of the glutamate treatment caused neuronal cell death through an alteration of Bax/Bcl-2 expression and translocation of mitochondrial apoptosis-inducing factor (AIF) to the cytoplasm of HT-22 cells. In addition, glutamate induced an increase in dephosphorylation of dynamin-related protein 1 (Drp1), mitochondrial fragmentation, and mitochondrial dysfunction. The pretreatment of Ole decreased Bax expression, increased Bcl-2 expression, and inhibited the translocation of mitochondrial AIF to the cytoplasm. Furthermore, Ole amended a glutamate-induced mitochondrial dynamic imbalance and reduced the number of cells with fragmented mitochondria, regulating the phosphorylation of Drp1 at amino acid residue serine 637. In conclusion, our results show that Ole has a preventive effect against glutamate-induced toxicity in HT-22 hippocampal neuronal cells. Therefore, these data imply that Ole may be an efficient approach for the treatment of neurodegenerative diseases. GRAPHICAL ABSTRACT: